Novel Mutations in the CLCN1 Gene of Myotonia Congenita: 2 Case Reports - Lakraj, Amanda Amrita (YJBM, 2013)
Introduction: Myotonia Congenita is an inherited myotonia that is due to a mutation in the skeletal muscle chloride channel CLCN1. These mutations lead to reduced sarcolemmal chloride conductance, causing delayed muscle relaxation that is evident as clinical and electrical myotonia. Methods: We report the clinical presentations of two individuals with Myotonia Congenita (MC). Results: Patient 1 has been diagnosed with the recessive form of MC, known as the Becker variant, and Patient 2 has been diagnosed with the dominant form of MC, known as the Thomsen variant. In both patients, the diagnosis was made based on the clinical presentation, EMG and CLCN1 gene sequencing. Patient 1 also had a muscle biopsy. Conclusions: Genetic testing in both patients reveals previously unidentified mutations in the CLCN1 gene specific to Myotonia Congenita. We report the salient clinical features of each patient and discuss the effects and common types of CLCN1 mutations and review the literature.